2014
DOI: 10.1086/677815
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth in the Australian freshwater mussel, Westralunio carteri, with an evaluation of the fluorochrome calcein for validating the assumption of annulus formation

Abstract: Growth and longevity of freshwater mussels (Unionida) are important for defining life-history strategies and assessing vulnerability to human impacts. We used mark-recapture and analysis of shell rings to investigate age and growth of the hyriid, Westralunio carteri, at 5 sites in southwestern Australia. We tested the utility of the in situ marker calcein for validating the assumption of annulus formation in adults. Calcein was incorporated into the shells of all recovered individuals, but it provided an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Gascho Landis et al (2013) and Gascho Landis & found that while increasing TSS resulted in reduced reproduction, there was no impact on growth rates. Research studies have used growth rates to evaluate changes in food source, inundation frequency, temperature, and release of environmental pollutants (Klunzinger et al, 2014;Negishi et al, 2012Negishi et al, , 2014aFritts et al, 2017). Growth rate has been found to differ between sexes of some mussel species where males often reach a larger maximum size, but this is not true for every species (Haag & Rypel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gascho Landis et al (2013) and Gascho Landis & found that while increasing TSS resulted in reduced reproduction, there was no impact on growth rates. Research studies have used growth rates to evaluate changes in food source, inundation frequency, temperature, and release of environmental pollutants (Klunzinger et al, 2014;Negishi et al, 2012Negishi et al, , 2014aFritts et al, 2017). Growth rate has been found to differ between sexes of some mussel species where males often reach a larger maximum size, but this is not true for every species (Haag & Rypel, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some long-lived mussel species can persist with infrequent and low recruitment events, even though juvenile survival can be quite low (e.g., Margaritifera auricularia; Prié et al, 2018). Other species require more frequent and even annual recruitment to maintain sustainable populations (Outeiro et al, 2008;Hastie et al, 2010;Klunzinger et al, 2014). Factors leading to low recruitment include juvenile habitat degradation and decreases in the populations of fish hosts (Bolotov et al, 2012).…”
Section: Demographymentioning
confidence: 99%
“…The lack of large mussels in the upstream reach during the present survey suggests that there was little or no recruitment before fishway installation 14 years ago. Age‐at‐length measurements for other populations of this species (Klunzinger, Beatty, Morgan, Lymbery, & Haag, ) show that SLs greater than 65 mm are not reached until 15+ years, at which point growth reaches an asymptote, with maximum lengths of 75–80+ mm not reached for 25–50+ years. Mussels ranging from 65–79 mm SL were common downstream of the weir in the mainstem of the river, but the largest individual found upstream was only 64.6 mm SL.…”
Section: Discussionmentioning
confidence: 99%